Switching to Aflibercept in Diabetic Macular Edema Not Responding to Ranibizumab and/or Intravitreal Dexamethasone Implant - Antoine Herbaut; Franck Fajnkuchen; Lise Qu-Knafo; Sylvia Nghiem-Buffet; Bahram Bodaghi; Audrey Giocanti-Auregan (Journal of Ophthalmology)
Purpose. To assess short-term functional and anatomical outcomes of refractory diabetic macular edema (DME) following a switch from ranibizumab or dexamethasone to aflibercept. Methods. We included retrospectively eyes with persistent DME after at least 3 ranibizumab and/or one dexamethasone implant intravitreal injections (IVI). The primary endpoint was the mean change in visual acuity (VA) at month 6 (M6) after switching. Results. Twenty-five eyes were included. Before switching to aflibercept, 23 eyes received a median of 9.5 ranibizumab, and among them, 6 eyes received one dexamethasone implant after ranibizumab and 2 eyes received only one dexamethasone implant. Baseline VA, before any IVI, was 52.9 ± 16.5 letters, and preswitch VA was 57.1 ± 19.6 letters. The mean VA gain was +8 letters (p=0.01) between preswitch and M6. The mean central retinal thickness was 470.8 ± 129.9 μm before the switch and 303.3 ± 59.1 μm at M6 (p=0.001). Conclusion. Switching to aflibercept in refractory DME results in significant functional and anatomical improvement. The study was approved by the France Macula Federation ethical committee (FMF 2017-138).